An analysis of the contribution of the look east policy to Zimbabwe’s economic growth from 2010 to 2015. - Nare, Bathabetsoe (Midlands State University, 2018)
The research explores the effects of the Look East policy to improving Zimbabwe’s ailing economy. The Look East Foreign Policy was mainly adopted as an economic experimental attempt by the government to improve the dead-locked economy that Zimbabwe assumed after it had been economically sanctioned by its Western foreign engagements, namely Britain, USA, Canada, and Australia, UN, EU and other allies of the Western bloc. The research was inspired by the current topical economic engagements that the Zimbabwean government is harmonizing with the Chinese government vis-à-vis, the sustainable economic development agenda that the ZANU-PF led government that the party adopted after it was re-elected into power following its landslide victory at the 2013 harmonised elections. The study follows the dependency theory which objects to explain the nature of relationship that Zimbabwe has with China. It is a qualitative analysis which borrows much of its information from written secondary documents and observations within the socio-economic structure of the Sino Zimbabwe relationship. In this case, the research is largely explanatory and evaluative of the historical, current and pushing factor to Zimbabwe’s adoption of the Look East policy. It is worth noting that the Look East policy encompasses a multi-state bloc, including China, Iran, Indonesia, India, Malaysia and Singapore but the study has been predominantly biased on Zimbabwe’s engagement with China because of the continued and active participation of the world’s second largest economy in Zimbabwe’s economic recovery strategy. Data analysis and presentation of the study is broadly explanatory, with the fusion of a quantitative presentation of Zimbabwe’s economic outlook. The research looks at the impacts of the Look East Policy to Zimbabwe’s economy from 2010 to 2016 so as to determine if the policy has brought about any notable development to the nation.